2017
DOI: 10.1016/j.cub.2017.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Frontoparietal Oscillatory Systems Support Working Memory

Abstract: Summary The ability to represent and select information in working memory provides the neurobiological infrastructure for human cognition. For 80 years, dominant views of working memory have focused on the key role of prefrontal cortex (PFC) [1–8]. However, more recent work has implicated posterior cortical regions [9–12], suggesting that PFC engagement during working memory is dependent on the degree of executive demand. We provide evidence from neurological patients with discrete PFC damage that challenges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 42 publications
7
117
0
Order By: Relevance
“…We did not observe an interaction of prediction and rhythmic stimulation, which implies a functional separation of top-down and bottomup systems supporting visual perception. Our results are in accordance with previous lesion studies, which indicated that high-level visual perception is PFC dependent (27,31), as well as reports suggesting that long-range endogenous delta activity may constitute a neural correlate of directed top-down control (15). For example, Johnson et al (31) reported that prefrontal damage diminished long-range top-down control that was associated with oscillatory activity in the delta-theta range (2-7 Hz).…”
Section: Discussionsupporting
confidence: 82%
“…We did not observe an interaction of prediction and rhythmic stimulation, which implies a functional separation of top-down and bottomup systems supporting visual perception. Our results are in accordance with previous lesion studies, which indicated that high-level visual perception is PFC dependent (27,31), as well as reports suggesting that long-range endogenous delta activity may constitute a neural correlate of directed top-down control (15). For example, Johnson et al (31) reported that prefrontal damage diminished long-range top-down control that was associated with oscillatory activity in the delta-theta range (2-7 Hz).…”
Section: Discussionsupporting
confidence: 82%
“…Frontal and parietal networks are emerging as important circuits for working memory and attention, and their absence is noteworthy. 41 The frontal abnormality is well appreciated in JME but disconnection to the parietal region has not been noted previously and may represent another underappreciated network deficit in JME that contributes to the wellknown dysexecutive function. [4][5][6] Furthermore, the identified widespread network disruptions may be contributed to the increasingly recognized generalized cognitive dysfunction, 7 increased rate of psychiatric complications, 8 and problematic long-term social function and employment status.…”
Section: Network Hubsmentioning
confidence: 86%
“…Specifically, alpha oscillatory activity exerts inhibitory influences on sensory cortical neuronal firing and excitation (Foxe & Snyder, 2011;Jensen & Bonnefond, 2013;Klimesch, Sauseng, & Hanslmayr, 2007). Furthermore, via long-range, posteriorfrontal projections, alpha oscillations mediate inhibitory bottom-up information flow from the sensory cortex to frontal regions to influence global neural activity (Hillebrand, et al, 2016;Johnson, et al, 2017;Sadaghiani & Kleinschmidt, 2016;Tang, et al, 2007). This long-range alpha connectivity plays a critical role in gating the entry of sensory input into downstream processing and, eventually, conscious awareness, thereby regulating perception, imagery, and working memory (Doesburg, Green, McDonald, & Ward, 2009;Jensen, Bonnefond, & VanRullen, 2012;Mathewson, et al, 2011;Samaha, Boutonnet, Postle, & Lupyan, 2018;Samaha & Postle, 2015).…”
Section: Introductionmentioning
confidence: 99%